Stochastic Modeling and Performance Optimization of Marine Power Plant with Metaheuristic Algorithms - Saini, Monika; Patel, Bhavan Lal; Kumar, Ashish (Journal of marine science and application, 2023)
For the successful operation of any industry or plant continuous availability of power supply is essential. Many of the large-scale plants established their power generation units. Marine power plant having two generators is also fall in this category. In this study, an effort is made to derive and optimize the availability of a marine power plant having two generators, one switch board and distribution switchboards. For this purpose, a mathematical model is proposed using Markov birth death process by considering exponentially distributed failure and repair rates of all the subsystems. The availability expression of marine power plant is derived. Metaheuristic algorithms namely dragonfly algorithm (DA), bat algorithm (BA) and whale optimization (WOA) are employed to optimize the availability of marine power plant. It is revealed that whale optimization algorithm outperforms over dragonfly algorithm (DA), and bat algorithm (BA) in optimum availability prediction and parameter estimation. The numerical values of the availability and estimated parameters are appended as numerical results. The derived results can be utilized in development of maintenance strategies of marine power plants and to carry out design modifications.